2019
DOI: 10.1038/s41598-019-44161-y
|View full text |Cite
|
Sign up to set email alerts
|

Gcm1 is involved in cell proliferation and fibrosis during kidney regeneration after ischemia–reperfusion injury

Abstract: In acute kidney injury (AKI), the S3 segment of the proximal tubule is particularly damaged, as it is most vulnerable to ischemia. However, this region is also involved in renal tubular regeneration. To deeply understand the mechanism of the repair process after ischemic injury in AKI, we focused on glial cells missing 1 ( Gcm1 ), which is one of the genes expressed in the S3 segment. Gcm1 is essential for the development of the placenta, and Gcm1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Both macrophage phenotypes promote kidney fibrosis [ 9 ]. M1 macrophages can cause local tissue damage by inducing the apoptosis of the surrounding cells and releasing proinflammatory substances such as tumor necrosis factor (TNF)-α and large amounts of nitric oxide (NO) through the inducible NO synthase (iNOS) [ 10 , 11 ]. These proinflammatory factors promote fibrosis through inhibited degradation of fibrinogen by the inhibition of matrix metalloproteinases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both macrophage phenotypes promote kidney fibrosis [ 9 ]. M1 macrophages can cause local tissue damage by inducing the apoptosis of the surrounding cells and releasing proinflammatory substances such as tumor necrosis factor (TNF)-α and large amounts of nitric oxide (NO) through the inducible NO synthase (iNOS) [ 10 , 11 ]. These proinflammatory factors promote fibrosis through inhibited degradation of fibrinogen by the inhibition of matrix metalloproteinases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…That was indicated by the cell’s density being higher compared to negative control with cells density of 70–80% confluence. The previous studies showed that TGF-β1 could induce fibroblast proliferation ( Kamejima et al, 2019 ; Prahastuti et al, 2019 ). The results of this study proved that quercetin was able to inhibit the cells proliferation of CKD cells model by reducing the TGF-β1 level.…”
Section: Discussionmentioning
confidence: 99%
“…3h). The destruction of renal tubular epithelial cells caused by I/R secondarily causes interstitial fibrosis of the renal parenchyma and rapidly reduces renal function 36 . Fibronectin deposition and TGF-b1 were analyzed to determine whether LPA treatment had any effect on the development and progression of fibrosis during IRI.…”
Section: Effect Of Lpa Treatment On Renal Histopathology and Fibrosis After I/rmentioning
confidence: 99%
“…LPA receptors expressed in the kidney (LPA 1 R, LPA 2 R and LPA 3 R) are coupled to a great variety of G proteins subsets that activate cell signaling cascades. Both the Gα q/11 sub-unit and the βγ sub-unit from G i/0 , dissociated from the trimeric conformation, modulate the PLC/PKC signaling pathway that is known to regulate the Na + transporters 15,31,36 . We measured PKC activity in the renal cortex of all experimental groups.…”
Section: Effect Of Lpa Treatment On Tubular Na+ Handling: the Influence On The Active Na + Transportersmentioning
confidence: 99%